THE ANALYSIS OF RECIPROCATING COMPRESSOR PK 60-150 FAILURE USING FAILURE MODE AND EFFECT ANALYSIS METHOD - Qosim, Nanang (Jurnal Penelitian Saintek, 2018)
The reciprocating compressor PK 60-150 is the most common type of compressor used in industries. The effect of each failure mode on the reciprocating compressor was analyzed using FMEA, so that the necessary action can be determined. Both increasing the operating time and preventing the damage of compressor are major concerns. This study was aimed to determine the problems that cause risk of safety, failure of compressor function, and shortening of compressor life time, so that maintenance and repair cost can be reduced. The result shows that the breaking of high wires and fuses, over heat and wear of the piston are the most affecting factors of compressor failure with RPN value of 64